Change in knee flexor torque after fatiguing exercise identifies previous hamstring injury in football players. (8th January 2018) - Lord, C.; Ma'ayah, F.; Blazevich, A. J.
Abstract : Muscular fatigue and interlimb strength asymmetry are factors known to influence hamstring injury risk; however, limb‐specific exacerbation of knee flexor (hamstrings) torque production after fatiguing exercise has previously been ignored. To investigate changes in muscular force production before and after sport‐specific (repeated‐sprint) and non‐specific (knee extension‐flexion) fatiguing exercise, and explore the sensitivity and specificity of isokinetic endurance (ie, muscle‐specific) and single‐leg vertical jump (ie, whole limb) tests to identify previous hamstring injury. Twenty Western Australia State League footballers with previous unilateral hamstring injury and 20 players without participated. Peak concentric knee extensor and flexor( 180°∙s −1 ) torques were assessed throughout an isokinetic endurance test, which was then repeated alongside a single‐leg vertical jump test before and after maximal repeated‐sprint exercise. Greater reductions in isokinetic knee flexor torque (−16%) and the concentric hamstring:quadriceps peak torque ratio (−15%) were observed after repeated‐sprint running only in the injured (kicking) leg and only in the previously injured subjects. Changes in (1) peak knee flexor torque after repeated‐sprint exercise, and (2) the decline in knee flexor torque during the isokinetic endurance test measured after repeated‐sprint exercise, correctly identified the injured legs (N = 20) within the cohort (N = 80) with 100% specificity and sensitivity. Decreases in peak knee flexor torque and the knee flexor torque during an isokinetic endurance test after repeated‐sprint exercise identified previous hamstring injury with 100% accuracy. Changes in knee flexor torque, but not SLVJ, should be tested to determine its prospective ability to predict hamstring injury in competitive football players.